ANALISIS KOGNITIF PESERTA PELATIHAN VOKASIONAL RENCANA USAHA DAN MANAJEMEN KEUANGAN KELOMPOK SWADAYA MASYARAKAT (KSM) BINAAN BDC SRIWIJAYA PALEMBANG - Thoyib, Ellys; Effendi, R.Y. (Fakultas Ekonomi Universitas IBA, 2019)
The purpose of the analysis is to find out the cognitions that appear in the cognitive system of vocational training participants in business plans and financial management of self-help groups (KSM) assisted by BDC Sriwijaya Palembang through the pre-test and post-test answers.There are 3 groups of knowledge behavior modes in participants' memories, namely positive mode 73%, negative 17% and doubtful 10%.Through the statement